What Makes a pDC: Recent Advances in Understanding Plasmacytoid DC Development and Heterogeneity - Musumeci, Andrea; Lutz, Konstantin; Winheim, Elena; Krug, Anne Barbara (Frontiers in Immunology, 2019)
Dendritic cells (DCs) are professional antigen presenting cells (APCs) that originate in the bone marrow and are continuously replenished from hematopoietic progenitor cells. Conventional DCs (cDCs) and plasmacytoid DCs (pDCs) are distinguished by morphology and function, and can be easily discriminated by surface marker expression both in mouse and man. Classification of DCs based on their ontology takes into account their origin as well as their requirements for transcription factor (TF) expression. cDCs and pDCs of myeloid origin differentiate from a common DC progenitor (CDP) through committed pre-DC stages. pDCs have also been shown to originate in large numbers from a lymphoid progenitor via an IL-7R+ Flt3+ precursor population containing cells with pDC or B cell potential. Technological advancements in recent years have allowed unprecedented resolution in the analysis of cell states, down to the single cell level, providing valuable information on the commitment and dynamics of differentiation of all DC subsets. However, the functional diversification of activated pDCs still raises the question whether different ontogenies generate restricted subsets, or fully differentiated cells still retain plasticity in response to challenges. The emergence of novel techniques for the integration of high-resolution data in individual cells promises interesting discoveries regarding DC development and plasticity in the near future.